Athlete transitions in a Norwegian professional football academy: transition experiences and parental support - Ohla, N.; Erikstad, M.; Sæther, S. A. (Soccer & Society, 2025)
Even though parents are expected to support their child in an academy football context, little is known about the impact of parental involvement in this period. The aim of the present study was to study perceptions of athletes` and their parents in their athletic transitions in a Norwegian professional football academy. Five parents and five players who had played in a Norwegian professional football academy between the ages of 16 and 18 years were interviewed in retrospect. Both parts described few athletic challenges, level of performance and playing in new positions were considered difficult to handle. Since only one of the players ended up playing professional football, we discuss in which degree the lack of pressure from most parents might have impacted on this fact. The results show however that the support the parents offer is considered important also when these players entered the professional club as junior players.